Efficacy and safety of tailored and dose‐dense adjuvant chemotherapy and trastuzumab for resected HER2‐positive breast cancer: Results from the phase 3 PANTHER trial. Issue 6 (18th December 2019) - Papakonstantinou, Antroula; Matikas, Alexios; Bengtsson, Nils Olof; Malmström, Per; Hedayati, Elham; Steger, Guenther; Untch, Michael; Hübbert, Laila; Johansson, Hemming; Hellström, Mats; Gnant, Michael; Loibl, Sibylle; et al.
Abstract : Background: Dose‐dense (DD) adjuvant chemotherapy improves outcomes in early breast cancer (BC). However, there are no phase 3 randomized data to inform on its combination with trastuzumab for patients with human epidermal growth factor receptor 2 (HER2)–positive disease. Methods: This was a protocol‐predefined secondary analysis of the randomized phase 3 Pan‐European Tailored Chemotherapy (PANTHER) trial. Women 65 years old or younger with node‐positive or high‐risk, node‐negative BC were randomized 1:1 to either tailored (according to hematologic nadirs) and DD epirubicin and cyclophosphamide followed by docetaxel or standard 5‐fluorouracil, epirubicin, and cyclophosphamide plus docetaxel every 3 weeks. Patients with HER2‐positive disease received 1 year of adjuvant trastuzumab. The primary endpoint was BC relapse–free survival. In addition, HER2‐positive patients and an equal number of HER2‐negative patients matched for age, treatment group, and institution who were enrolled at Swedish sites were asked to participate in a predefined study of cardiac safety and underwent echocardiography or multigated acquisition scanning and electrocardiography at the baseline and at 4 and 6 years of follow‐up. Results: There were 342 HER2‐positive patients; 335 received at least 1 dose of trastuzumab, and 29 patients discontinued trastuzumab prematurely. Relapse‐free survival was not statistically significantly in favor of the tailored and DD group (hazard ratio, 0.68; 95% confidence interval, 0.37‐1.27; P = .231). Cardiac outcomes after 4 and 6 years of follow‐up did not differ significantly between HER2‐positive and HER2‐negative patients or between the 2 treatment groups. Conclusions: The combination of DD chemotherapy and trastuzumab decreased the relative risk for relapse by 32% in comparison with standard treatment, a statistically nonsignificant difference. Its efficacy and safety merit further evaluation as part of both escalation and de‐escalation strategies. Abstract : A combination of tailored and dose‐dense chemotherapy and trastuzumab is feasible without significant excess cardiotoxicity. A favorable effect of tailored and dose‐dense chemotherapy in combination with trastuzumab in high‐risk human epidermal growth factor receptor 2–positive breast cancer is seen, but it is not statistically significant.